1981
DOI: 10.1111/j.1744-313x.1981.tb00758.x
|View full text |Cite
|
Sign up to set email alerts
|

MHC GENE CONTROL OF GROWTH OF AVIAN SARCOMA VIRUS‐INDUCED TUMOURS IN CHICKENS: A STUDY ON THE ROLE OF VIRUS STRAIN

Abstract: Summary A comparison was made of growth patterns (progression/regression) of tumours induced by different strains of avian sarcoma virus in two partially congenic inbred lines of chickens homozygous for different MHC haplotypes. In each instance studied, the ability to regress tumours was shown to be a dominant trait controlled by MHC‐linked genes. The results also demonstrate a difference in growth pattern between tumours induced by different strains of virus in an inbred line as well as different growth patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Senseney et al [37] in a cross segregating for two haplotypes (B Q and B 17 ) found no effect of MHC on the regression of tumors at a high dose of virus but an effect at a lower dose of the same virus and in the same genetic stock with an allelic complementation between the two alleles, the heterozygote state showing an advantage towards tumor regression. The superiority of other heterozygote combination were found elsewhere [6,27,39]. The effect of the resistance genes may clearly depend on the degree of pathogenicity of the virus.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Senseney et al [37] in a cross segregating for two haplotypes (B Q and B 17 ) found no effect of MHC on the regression of tumors at a high dose of virus but an effect at a lower dose of the same virus and in the same genetic stock with an allelic complementation between the two alleles, the heterozygote state showing an advantage towards tumor regression. The superiority of other heterozygote combination were found elsewhere [6,27,39]. The effect of the resistance genes may clearly depend on the degree of pathogenicity of the virus.…”
Section: Discussionmentioning
confidence: 86%
“…Even more interesting would be to combine these different Rfp-Y genotypes with different B genotypes since complementing effects have been suggested by LePage et al [26]. Also, as found for the MHC, interactions between the effect of the Rfp-Y system on the fate of RSV tumors and other factors like age at inoculation [24], virus strain [27] or dose of virus [37] should be investigated. Senseney et al [37] in a cross segregating for two haplotypes (B Q and B 17 ) found no effect of MHC on the regression of tumors at a high dose of virus but an effect at a lower dose of the same virus and in the same genetic stock with an allelic complementation between the two alleles, the heterozygote state showing an advantage towards tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest is the observation of McBride et al (1981) on the role of the virus strain. They concluded that birds of a given MHC genotype may be either resistant or highly susceptible after challenge with closely related strains of virus of the same antigenic subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Adding further complexity, McBride et al (1981) concluded that a given B complex may be either resistant or susceptible, depending on the strain or subgroup of the tumor-induced virus. More specifically, they suggested that the gene product, P60 sre , of the viral gene src, expressed on the tumor cells, is a plausible candidate for the immunogenetic target of the MHC-linked rejection response.…”
Section: Introductionmentioning
confidence: 97%
“…Apparently the frequency of regression at these ages was associated with the development of immunological maturity (Cotter et al, 1973). McBride et al (1981) investigated the degree to which tumour growth was mod-ified by the strain of the sarcoma-inducing virus. They suggested that exposure of adults to a variety of complex, naturally-occurring antigens prior to inoculation may have resulted in more efficient tumour destruction by the host immune system.…”
Section: Other Factors Influencing Regressionmentioning
confidence: 99%